Endometriosis and psychosymptomatogy: the impacts of a challenging disease (Research, Society and Development, 2022)
Introduction: Endometriosis is a benign and chronic estrogen-dependent gynecological disease. Due to the numerous symptoms it can cause, it has a significant impact on the quality of life of women affected in different areas: in mental health, in their interpersonal relationships and at work. Objective: This study seeks to understand how endometriosis can affect the quality of life of affected women and what can be done so that the disease and its repercussions can become more bearable for the patient. Methodology: This is an integrative literature review through articles published in the PubMed, Scielo database and in scientific journals between 2006 and 2021. Results: Endometriosis has already been associated with a wide range of symptoms with high intensity including pain, pelvic pain and infertility and, therefore, can lead to a decrease in the patient's quality of life. This loss can include physical pain, psychological and economic impacts, social isolation, depression, anxiety and mood swings, pressure and irritability. Therefore, that improving their autonomy and body awareness, reducing stress and performing physical exercises improve the physical quality of the patient with the disease. In addition to the diagnosis, in addition to the symptomatic and physical treatment, psychological and multiprofessional help for patients is important. Conclusion: Therefore, it is clear that the condition of endometriosis has a negative impact on the quality of life of the affected woman. In addition, it is essential to reiterate the individualized and multidisciplinary follow-up of this patient.